Mastery matters most: How mastery and positive relations link attachment avoidance and anxiety to negative emotions. Issue 5 (3rd July 2016) - Paech, Juliane; Schindler, Ines; Fagundes, Christopher P.
Abstract : Attachment avoidance and anxiety are associated with negative emotions. However, the mechanisms underlying these associations are not fully understood. We investigated environmental mastery and positive relations with others as two mechanisms behind the attachment–emotion link in a sample of 343 adults. As predicted, attachment avoidance and anxiety were related to greater fear, hostility, envy and depression through lower mastery. Contrary to our hypothesis, positive relations mediated only the attachment–depression link. In addition, by adopting a moderated mediation approach, we were able to show that mastery mattered most for individuals high on avoidance: The indirect effect of avoidance through lack of mastery on fear, hostility and depression (but not on envy) increased with higher avoidance scores. Contrary to our predictions, poor relationships did not matter more as sources of negative emotions as anxiety increased. These findings underscore that the emotional life of avoidantly attached individuals is especially jeopardised by poor mastery.